Discourse and Communication Translation Model and Translation Strategy: an Experimental Study - T. A. Volkova (Научный диалог, 2021)
A longitudinal mediated asynchronous procedural experimental study is presented, the purpose of which is to demonstrate the correlation between the discourse and communication translation model and the translation strategy. Subjects’ retrospective self- and peer commentaries are analyzed. It is shown that the subjects’ evaluation of translation solutions implemented in the target text is based on their own translations and translating objectives, as reflected both in the self- and peer commentaries. The following translation dominants are revealed by the experiment: target text audience (recipient); source text style; source text type (genre), target text type (genre); individual linguistic features of the target text; discourse goals; discourse nodal points; discourse values; communication functions; typical properties of communication; and communication strategies. It is demonstrated that the discourse and communication translation model has a positive effect on the consistency and the degree of detail of source text analysis, and allows translators to make more informed decisions. It is noted that if changes in the target text are mainly caused by the translator’s decision to make corrections when re-accessing the text, these changes reflect the described translation dominants. It is shown that the model indirectly affects the quality of translation, depending on the degree of implementation of the translation strategy, taking the additional factors into account.